Can the experimental study of religion be advanced using a Bayesian predictive framework? - van Elk, Michiel (Religion, brain & behavior, 2017)
We propose a Bayesian framework as an important theoretical and methodological tool to improve the scientific study of religion. At a theoretical level, the Bayesian predictive processing framework has the potential to provide a unifying account of religious beliefs and experience by stressing the central role of error monitoring and error correction in belief maintenance. At a methodological level, Bayesian statistics are needed to provide the extraordinary evidence for the extraordinary theoretical claims regarding the causes and consequences of religion.